A price to pay: Turkish and Northern American retaliation for threats to personal and family honor. Issue 6 (30th July 2015) - Uskul, Ayse K.; Cross, Susan E.; Günsoy, Ceren; Gerçek‐Swing, Berna; Alözkan, Cansu; Ataca, Bilge
<x xml:space="preserve">Abstract</x> Two studies investigated retaliatory responses to actual honor threats among members of an honor culture (Turkey) and a dignity culture (northern United States). The honor threat in these studies was based on previous research which has shown that honesty is a key element of the conception of honor and that accusations of dishonesty are threatening to one's honor. In both studies, participants wrote an essay describing the role of honesty in their lives and received feedback on their essay accusing them of being dishonest (vs. neutral feedback). Turkish participants retaliated more strongly than did northern U.S. participants against the person who challenged their honesty by assigning him/her to solve more difficult tangrams over easy ones (Study 1) and by choosing sensory tasks of a higher level of intensity to complete (Study 2). Study 2 added a relational honor condition, in which participants wrote about honesty in their parents' lives and examined the role of individual differences in honor values in retaliation. Endorsement of honor values significantly predicted retaliation among Turkish participants in the relational honor attack condition, but not among northern U.S. participants. Aggr. Behav. 41:594–607, 2015. © 2015 Wiley Periodicals, Inc.